When Artificial Intelligence Formulates Laws: Are We Redefining the Scientific Method? (SciComm Report, 2025)
The emergence of the AI-Newton model, capable of autonomously formulating physical laws from experimental data without prior knowledge, marks a paradigm shift in the philosophy and practice of science. Unlike conventional AI systems focused on pattern recognition, AI-Newton constructs theoretical frameworks and derives universal principles, such as energy conservation, mimicking and even surpassing human scientific heuristics. This development challenges the anthropocentric conception of science as a uniquely human endeavor, raising fundamental epistemological questions. Are we witnessing an extension or a radical transformation of the scientific method? As AI begins to automate concept formation and theoretical innovation, the role of human comprehension and meaning-making in science is brought into question. Rather than opposing this shift, the scientific community must confront the philosophical implications of a future where machines not only support but potentially outpace human discovery.
Keywords: Scientific Method; Artificial Intelligence; Epistemology; AI-Newton; Knowledge Automation; Philosophy of Science; Law Discovery; Human-AI Interaction